The Impact of Digital Money on Lifestyle Patterns and Financial behavior among Residents of Dumai City - Chandra Utama Telaumbanua; Adinda Agusti Ayu; Diah Geraldin Simanjuntak; Lili Suryani; Hildawati Hildawati (CV. Civiliza Publishing, 2026)
This study aims to analyze the impact of digital money use on shaping lifestyle patterns and financial behavior among the residents of Dumai City. Employing a descriptive quantitative approach, data were collected via questionnaires distributed to 77 respondents from diverse educational, occupational, and age backgrounds. The analysis was carried out within the Technology Acceptance Model (TAM) framework, which includes perceived usefulness, perceived ease of use, attitude, and behavioral intention. The results show that the majority of respondents agreed or strongly agreed that digital money offers benefits and convenience and that it influences attitudes and intentions toward its use. These findings confirm that digital money plays a significant role in shaping the lifestyles of Dumai residents, particularly by improving transaction efficiency and altering financial behavior. Nevertheless, the adoption of digital money also requires financial awareness to avoid encouraging excessive consumerist behavior. This study is expected to provide both theoretical and practical contributions to understanding the role of digital money in shaping lifestyle patterns and financial behavior in society during the digital era.